Reviewed book: Asta MIKALAUSKIENE, Dalia STREIMIKIENE, Ignas MIKALAUSKAS (2026), Climate Change and Responsible Consumption: From Crisis to Conscious Consumer Choices, Springer Cham, 252 p. - Siksnelyte-Butkiene, Indre (Transformations In Business & Economics, 2026)
Reviewed book: Asta MIKALAUSKIENE, Dalia STREIMIKIENE, Ignas MIKALAUSKAS (2026), Climate Change and Responsible Consumption: From Crisis to Conscious Consumer Choices, Springer Cham, 252 p.
Keywords: book review